2021
DOI: 10.3389/fimmu.2020.617804
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signaling in Controlling Macrophage and T Cell Functions During Atherosclerosis Development

Abstract: Atherosclerosis is a hardening and narrowing of arteries causing a reduction of blood flow. It is a leading cause of death in industrialized countries as it causes heart attacks, strokes, and peripheral vascular disease. Pathogenesis of the atherosclerotic lesion (atheroma) relies on the accumulation of cholesterol-containing low-density lipoproteins (LDL) and on changes of artery endothelium that becomes adhesive for monocytes and lymphocytes. Immunomediated inflammatory response stimulated by lipoprotein oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 152 publications
1
11
1
Order By: Relevance
“…Age and LDL-C increasing the risk of atherosclerosis has been confirmed by many studies [23,25], and the results of this study also confirmed this. In addition, the results of this study showed that the course of gout increased the risk of CCAIMT thickening, which was inconsistent with the results of the study by Mariano Andrés [16].…”
Section: Ccaimt and Plaquesupporting
confidence: 89%
See 1 more Smart Citation
“…Age and LDL-C increasing the risk of atherosclerosis has been confirmed by many studies [23,25], and the results of this study also confirmed this. In addition, the results of this study showed that the course of gout increased the risk of CCAIMT thickening, which was inconsistent with the results of the study by Mariano Andrés [16].…”
Section: Ccaimt and Plaquesupporting
confidence: 89%
“…In addition, the results of this study showed that LY% was a protective factor for CCAIMT, and LY% could reduce the risk of CCAIMT thickening. Studies have shown that macrophages and LY % play a key role in the development of atherosclerosis and can provide signals for the potential pro-inflammatory background of atherosclerosis [23]. The results of this study were inconsistent with the aforementioned pathological process.…”
Section: Ccaimt and Plaquecontrasting
confidence: 83%
“…response and lipid uptake tightly connects with atherosclerotic progression (Ferrari et al, 2020). Specifically blocking these undesirable functions in macrophages may be an attractive choice for alleviating AS and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is still the leading cause of death all over the world, and AS is one of the major etiologies ( Kuznetsova et al, 2020 ). Macrophage-mediated inflammatory response and lipid uptake tightly connects with atherosclerotic progression ( Ferrari et al, 2020 ). Specifically blocking these undesirable functions in macrophages may be an attractive choice for alleviating AS and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome activation and IL-1β production are factors that contribute to HIV-associated inflammation, and these are strongly implicated in the development of atherosclerosis and hypertension [ 78 , 79 ]. Activation of the NLRP3 inflammasome and release of IL-1β are strongly tied to purinergic signaling, particularly P2X 7 R stimulation [ 78 , 80 ]. In addition, the inflammasome system may contribute to the loss of CD4 + T-cell populations and overall lack of immune recovery seen in PWH [ 81 ].…”
Section: Impact Of Adenosine Signaling On Inflammation and Comorbidities In Treated Human Immunodeficiency Virusmentioning
confidence: 99%